Significance of tumour regression in lymph node metastases of gastric and gastro‐oesophageal junction adenocarcinomas. (13th May 2020) - Reim, Daniel; Novotny, Alexander; Friess, Helmut; Slotta‐Huspenina, Julia; Weichert, Wilko; Ott, Katja; Dislich, Bastian; Lorenzen, Sylvie; Becker, Karen; Langer, Rupert
Abstract: The presence of lymph node (LN) metastases is one of the most important negative prognostic factors in upper gastrointestinal carcinomas. Tumour regression similar to that in primary tumours can be observed in LN metastases after neoadjuvant therapy. We evaluated the prognostic impact of histological regression in LNs in 480 adenocarcinomas of the stomach and gastro‐oesophageal junction after neoadjuvant chemotherapy. Regressive changes in LNs (nodular and/or hyaline fibrosis, sheets of foamy histiocytes or acellular mucin) were assessed by histology. In total, regressive changes were observed in 128 of 480 patients. LNs were categorised according to the absence or presence of both residual tumour and regressive changes (LN−/+ and Reg−/+). 139 cases were LN−/Reg−, 28 cases without viable LN metastases revealed regressive changes (LN−/Reg+), 100 of 313 cases with LN metastases showed regressive changes (LN+/Reg+), and 213 of 313 metastatic LN had no signs of regression (LN+/Reg−). Overall, LN/Reg categorisation correlated with overall survival with the best prognosis for LN−/Reg− and the worst prognosis for LN+/Reg− ( p < 0.001). LN−/Reg+ cases had a nearly significant better outcome than LN+/Reg+ ( p = 0.054) and the latter had a significantly better prognosis than LN+/Reg− ( p = 0.01). The LN/Reg categorisation was also an independent prognostic factor in multivariate analysis (HR = 1.23; 95% CI 1.1–1.38; p < 0.001). We conclude that the presence of regressive changes after neoadjuvant treatment in LNs and LN metastases of gastric and gastro‐oesophageal junction cancers is a relevant prognostic factor.